Implementation Of Naruto Shippuden Anime-Based Learning Media To Improve Students' Understanding Of Informatics At SMPN 3 Bolo - muhaimin muhaimin; Hardyanti Hardyanti; Lisda Ramdhani (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to analyze the effectiveness of Naruto Shippuden anime-based learning media in improving students’ understanding and learning motivation in Informatics at SMPN 3 Bolo. The background of this research lies in students’ difficulties in comprehending abstract informatics concepts and the lack of engaging learning media, which leads to low participation. This study employed a descriptive qualitative approach with 20 students as subjects. Data were collected through interviews, observations, questionnaires, and documentation of pre-test and post-test results.The findings show that the implementation of this media was significantly successful. Quantitative results demonstrated a substantial improvement in post-test scores compared to pre-test scores. Qualitatively, students showed positive responses, with increased enthusiasm, active participation, and concentration. They perceived the material as easier to understand because it was linked to the storyline and characters of the anime, such as the analogy of “Jutsu” for data processing. The majority of students (93.3%) also recommended the use of this media for future learning.In conclusion, Naruto Shippuden anime-based learning media proved effective in enhancing students’ understanding and motivation. This approach represents an innovative pedagogical strategy that aligns with students’ interests and the principles of the Merdeka Curriculum, offering a solution for more contextual, adaptive, and student-centered learning.